Vegetative and Fecundity Fitness Benefit Found in a Glyphosate-Resistant Eleusine indica Population Caused by 5-Enolpyruvylshikimate-3-Phosphate Synthase Overexpression - Li, Zhiling; Li, Xiangju; Cui, Hailan; Zhao, Guodong; Zhai, Dan; Chen, Jingchao (Frontiers in Plant Science, 2021)
Fitness is an important trait in weed species that have developed herbicide resistance, including resistance to the popular herbicide glyphosate. Fitness cost is commonly found in weeds with glyphosate resistance, which is caused by target-site mutations. In this study, the vegetative and fecundity fitness traits in a glyphosate-resistant (GR) Eleusine indica population caused by 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) overexpression were investigated under glyphosate-free conditions. The results showed that the resistance index of the population resistant (R) to glyphosate compared with that of the population susceptible (WT) to it was approximately 4.0. Furthermore, EPSPS expression level in the R plants was 20.1–82.7 times higher than that in the WT plants. The dry weight of the R population was significantly higher than that of the WT population at the later growth stage after planting; a similar trend was observed for leaf area. In addition, seed production in the R population was 1.4 times higher than that in the WT population. The R and WT populations showed similar maximum germination rates and T50 values. UPLC-MS/MS was performed for the metabolic extracts prepared from the leaves of R and WT populations to address changes in the metabolome. A total of 121 differential metabolites were identified between R and WT individuals. The levels of 6-hydroxy-1H-indole-3-acetamide and indole acetaldehyde, which are associated with auxin synthesis, were significantly higher in plants of the R population than in those of the WT population. However, some secondary metabolite levels were slightly lower in the R population than in the WT population. To conclude, in this study, vegetative and fecundity fitness benefits were found in the GR E. indica population. The results of metabolome analysis indicate that the increase in 6-hydroxy-1H-indole-3-acetamide and indole acetaldehyde levels may be the result of fitness benefit. Further studies should be conducted to confirm the functions of these metabolites.